Fatigue behavior of ultrafine grained triplex Al0.3CoCrFeNi high entropy alloy. (1st January 2019) - Liu, Kaimiao; Komarasamy, Mageshwari; Gwalani, Bharat; Shukla, Shivakant; Mishra, Rajiv S.
Abstract: Ultrafine grained (UFG) alloys suffer from limited strain hardening hence reduced ductility. Incorporation of deformation twinning can overcome this limitation. An Al0.3 CoCrFeNi high-entropy alloy was thermo-mechanically processed to yield a UFG triplex microstructure (davg : 0.71 ± 0.35 μm) with FCC, and hard B2 and sigma phases. The annealed material exhibited an exceptional strength-ductility combination with ultimate tensile strength (UTS) of 1.1 GPa and elongation of 25%. Furthermore, the alloy showed excellent fatigue resistance with an endurance limit of 0.43 UTS. Remarkable mechanical properties are attributed to the formation of extensive deformation nanotwins and increased dislocation accumulation capability. Graphical abstract: Unlabelled Image